Racial Disparity in Antibody Against High Prevalence Antigen; Anti-U. (9th November 2022) - Abdelmonem, M; Cai, W; Yunce, M; Tang, M; Shan, H; Cabungan, M
Abstract: Introduction/Objective: Anti-U is an IgG antibody directed against the U antigen, which usually forms after exposure to U antigen via blood transfusion and/or pregnancy. U antigen is located on glycophorin B (GYPB) as part of the MNS blood group system. Approximately 2% of the African American population lacks this antigen, making them prone to developing anti-U. Anti-U can cause hemolytic disease of fetus and newborn (HDFN) and hemolytic transfusion reactions (HTR). Methods/Case Report: A 60-year-old African American male underwent aortic valve surgery. The patient was A Pos with a negative antibody screen. During surgery, the patient was transfused with 3 random units of packed red blood cells (PRBCs). The postoperative course was uncomplicated, and the patient was discharged home. 6 months later, the patient was admitted for another procedure and was expected to require blood products. Thus, a type and screen test was ordered, revealing pan reactivity on screening cells. This prompted further investigation. Antibody detection was performed with the solid-phase technique followed by the tube method with Polyethylene glycol (PEG) as an enhancement medium. PEG technique is the next choice of method if the solid phase requires extended antibody work up, which was the case in our patient. PEG tube method successfully identified Anti-U, and the patient's phenotype was confirmed to be U negative. Results (if a Case Study enter NA): N/A. Conclusion: It is imperative to stress the importance of racial disparity while investigating antibodies against high prevalence. In our case, our suspicion was high for Anti-U, given that patient was of African American descent. Tube methods with PEG and Solid Phase techniques are usually used for antibody identification. It is recommended that patients with rare antibodies carry an Antibody ID card indicating the rare antibody they have to prevent further exposure.